2017
DOI: 10.1287/mnsc.2015.2394
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the Devil You Don’t Know: Evidence for Limited Sensitivity to Sample Size–Based Uncertainty When It Offers an Advantage

Abstract: Abstract. Many decision makers seek to optimize choices between uncertain options such as strategies, employees, or products. When performance targets must be met, attending to observed past performance is not enough to optimize choices-option uncertainty must also be considered. For example, for stretch targets that exceed observed performance, more uncertain options are often better bets. A significant determinant of option uncertainty is sample size: for a given option, the smaller the sample of information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Surprisingly, participants expressed higher confidence in their judgements when the number of coin tosses was small, whereas from a statistical perspective, confidence should be lower for smaller samples. Several studies have found that people’s inferential (e.g., Kutzner et al, 2017), perceptual (e.g., Kvam & Pleskac, 2016), and preferential judgements (e.g., Powell et al, 2017) are less sensitive to sample sizes than expected by normative models.…”
Section: How Does Sample Size Influence Preferences?mentioning
confidence: 93%
“…Surprisingly, participants expressed higher confidence in their judgements when the number of coin tosses was small, whereas from a statistical perspective, confidence should be lower for smaller samples. Several studies have found that people’s inferential (e.g., Kutzner et al, 2017), perceptual (e.g., Kvam & Pleskac, 2016), and preferential judgements (e.g., Powell et al, 2017) are less sensitive to sample sizes than expected by normative models.…”
Section: How Does Sample Size Influence Preferences?mentioning
confidence: 93%
“…For instance, participants estimated that a large hospital with 45 births daily and a small hospital with 15 births daily would have a similar number of days on which more than 60% of births were boys, whereas in reality, the larger hospital is much less likely to deviate from the mean of 50% than the smaller hospital (Kahneman & Tversky, 1972). People fail to realize that the means from smaller samples are likely to be more variable than means from larger samples drawn from the same population, indicating that people are largely insensitive to variations in the sample size when making judgments about variability in the sample mean (Kahneman & Tversky, 1972; Kutzner et al, 2016). Research on decision-making based on experiences has also found that people have higher confidence in data from single, isolated observations or anecdotes than data from repeated observations summarized in the form of statistical evidence (Obrecht et al, 2007), indicating that people do not take the sample size into consideration when interpreting data.…”
Section: Two Streams Of Researchmentioning
confidence: 99%